‘Walk softly and carry no stick': Culture, opportunity and irresponsible risk-taking in the Irish banking sector - McGrath, Joe (European journal of criminology, 2020)
This article examines the generative conditions giving rise to the commission of irresponsible risk-taking in the Irish banking sector using differential association and opportunity theories. This framework is used as a lens to demonstrate how, at both an individual and a group level, ideas, beliefs, expectations, rewards and punishments had a causal impact on banking culture, where competitive and aggressive risk-taking was prioritised, networked and routinised. Though differential association theory and opportunity theory are usually treated as separate (and somewhat opposing) perspectives, this article offers a framework that integrates them both. It employs differential association only as a partial explanation, explaining that wrongdoing does not occur only where there is an excess of ‘definitions' favouring it; it occurs when capable guardians are removed or undercut. The opportunity perspective is adopted to examine how the absence of credible supervision and enforcement in the financial services sector created situational conditions that facilitated wrongdoing. Moreover, opportunity theory is valuable in this context because it explains that the extent to which protection is offered often depends on political processes to create a structure and culture of enforcement and prosecution of offenders. Prior to the crisis, Ireland was championing light-touch regulation, advertising itself as an attractive place to do business, in which there was insufficient political support for tough sanctions to address financial wrongdoing.